A study on solutions to exchange the building projects data between BIM platforms - Kock, Ming Tai (2018)
Digitalisation of building construction is evident. Inclusion of information technology in various stage of building life cycle has undoubtedly leveraged the value added of the every project undertaken. Absence of conformity among the key software providers is the prime cause of restricted model mobility. In the face of such issue, IFC was brought in as universal file format that bridges various BIM authoring applications together. Notwithstanding, massive data losses and instabilities are found plaguing the model exchange process, inducing mixed sentiments against this promising exchange means. This paper hypothesizes the possible causes of the defective model transfer through IFC. Also, a systematic comparison was introduced to semantically quantify the information loss. For ease model information comparison, .NET applications were formulated using C# to interact with the Autodesk Revit and Tekla Structure to export model object data to an Excel Sheet, while the conveyance of IFC model data into Excel Sheet was accomplished via simpleBIM, a BIM model enriching software. In this paper, we showcase some indicators from model data derived that can be utilised to predict the success rate of the individual object exchange. Discussions centre primarily on how the interaction between model objects (overlapping of objects), the object geometry (intricate non-linear profile) and the absence of a standardised modelling practice guidelines may impact the consistency of data transfer across different commercial BIM tools constitutes the major part of the paper. The analysis on the derived model information strongly suggests that the generation of IFC equivalent from the original model is based on the model view rather than the model object parameters. Therefore, it results in the occurrence of data asymmetries in the model upon transfer.